Importance of detecting thyroid pathology associated with COVID - Nascimento Machado, Moisés Castro; Laube, Dr. Gerardo (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Background: COVID-19 (SARS-CoV-2) infection can cause the development of various pathologies, some of which affect the endocrine system. This article provides a narrative review of the association between COVID-19 and thyroid conditions, describing the epidemiology, pathophysiological aspects, clinical and laboratory manifestations, treatment and prognosis. Material and methods: The methodology of this work is based on the compilation of information from previous studies, scientific articles and postgraduate studies published in the database: Scielo, PubMed, Intramed, WHO, Ministry of Health of Argentina). Results: COVID-19 infection can affect thyroid function and cause thyroid-related symptoms such as neck pain, malaise, and thyroid dysfunction. Some studies have documented cases of subacute thyroiditis associated with COVID-19. The thyroid gland may be vulnerable to COVID-19 infection and thyroid hormones may influence the immune response against COVID-19. Conclusion: COVID-19 can activate the immune system and cause hyperactivity, sometimes leading to the new onset of autoimmune disorders. The severity of SARS-CoV-2 infection may be affected by the state of the thyroid gland before and during infection, but the dependencies are not fully understood. There is no evidence to suggest that hypothyroidism, hyperthyroidism, and autoimmune thyroid diseases have a direct impact on the severity of COVID-19. However, reduced serum free triiodothyronine levels can be used as an indicator of mortality in SARS- CoV-2-positive patients. Further evaluation is required to determine the relationship between subacute thyroiditis and COVID-19